The Effect of Spaced Repetition Strategy on Students’ Vocabulary Mastery - Silvana Inul Aprilia; Lollo Rosa Lubis; Melwan Ady Rezki Harahap (English Language Education, Universitas Internasional Batam, 2026)
This research was conducted to investigate the effect of the Spaced Repetition Strategy on the vocabulary achievement of seventh-grade students at SMP Negeri 11 Padangsidimpuan. A quantitative method with a pre-experimental one-group pre-test and post-test design was applied in this study. The sample comprised 55 students who were selected using the total sampling technique. Data were obtained through observation checklists and a vocabulary assessment. The results showed that the students’ average pre-test score was 54.91, which improved to 74.94 in the post-test following the application of the Spaced Repetition Strategy. Furthermore, the observation of the strategy's implementation yielded a score of 90%, classified as “Very Good.” The hypothesis test demonstrated that the calculated t-value exceeded the critical t-value at the 5% level of significance (13.73 > 2.01). This finding confirmed that the alternative hypothesis was accepted, whereas the null hypothesis was rejected. Consequently, it can be inferred that the Spaced Repetition Strategy significantly enhanced students’ vocabulary mastery and supported more effective vocabulary retention through scheduled and repeated review practices.